The Influence of the Learning Environment on Student Motivation - Muh. Nasrullah; Sri Andira; Isgunandar Isgunandar (International Journal of Administration and Education (IJAE), 2024)
A learning environment is a diverse platform where users interact with each other and learn something new. In order for the growth and development of students to be carried out effectively and efficiently and for the goals to be fully achieved, an ideal learning environment must be built and maintained. If there is a good teaching and learning environment, students will be more interested in following the learning steps. The purpose of this study is to study how college students learn affects their motivation to learn. This quantitative study shows cause and effect. A simple random sample method was used to select 53 subjects in this study. Questionnaires, observations, and documentation are data collection methods. Descriptive data analysis and inferential statistical analysis were used. The results show that the learning environment in the Office Administration Study Program, Faculty of Social Sciences and Law, State University of Makassar is in the fairly good category with three indicators: family environment, school or campus environment, and community environment. The existence of desire and desire to succeed are six indicators that show that learning motivation is in the "Quite High" category. Students must have motivation and need for learning, future ideals and expectations, awards, engaging activities, and a conducive learning environment. The relationship between variables is strong, according to the results of the product moment correlation test. In addition, according to the results of a simple linear regression analysis, the learning environment has a positive and significant effect on students' learning motivation.